Pengaruh Pertumbuhan Penjualan, Profitabilitas dan Aktivitas terhadap Financial Distress - Harefan Arief; Chairiel Oktaviar; Eko Tama Putra Saratian; Mochammad Soelton (Neolectura, 2023)
The condition of financial distress is a condition that precedes which a business will run in condition of incapacity or business failure and will eventually lead to the worst condition in business, which is bankruptcy. Bankruptcy and business failure are a scourge and common in a competitive business environment. The problem of financial difficulties arises when the company can no longer fulfill its payment commitments or cannot fulfill its debts (Michael, et al, 2020). Within the company, the bankruptcy analysis can be useful to anticipate as an early warning of bankruptcy conditions and for business continuity or sustainability. So that the risk of bankruptcy can be minimized and improvements can be made immediately. There are several models that can be used in analyzing a company's Financial Distress, the most widely used is the Altman model. The study aims to analyze and identify the influence of fundamental factors represented by ratios such as Sales Growth Analysis, ROA Ratio, Current Ratio, and Activity ratio on Financial Distress conditions. This research was conducted on financial statements of oil and gas mining sector company listed on the Indonesia stock exchange. Data was collected using data panel with multiple linear regression technique analysis. Data was proceed using Eviews 12. The result show Sales growth, ROA, Current Ratio and TATO ratio have a partially significant effect on Financial Distress. Sales growth ROA, Current Ratio and TATO ratio together and a simultaneous have an effect on Financial Distress.